Pengaruh Terpaan Iklan E-Commerce Blibli.com terhadap Minat Beli Konsumen - Agung Millenienbun; H.H Daniel Tamburian (Kiwari, 2022)
In the era 21st century, we are experiencing a massive growth in digital technology, especially related to online transaction which also commonly called e-commerce. Blibli.com is one of the example of well known e-commerce channel in Indonesia owned by PT. Global Digital Niaga. This company has been providing board selection of both physical and digital products on its site. Blibli.com is also participating aggresively in many marketing platforms, name it television, radio, print media, billboard, social media and more. This thesis has goal to validate the leveraging influence of advertising exposure toward customers’ buying intention. This thesis is using quantitative approach with method of data collected by quesionaire. Sample population is taken from the Students of University of Tarumanegara with technigue is using simple random sampling out from 100 respondents. Analysis data is using Normality Test, Simple Linear Regretion Test, T Test, and Determination Coeficient Test. Results have been validated that the advertiising exposure from Blibli.com is giving out leveraging influence and yielding good impact from customers’ buying intention which the T test is showing count of 7,611 > t table 1,984. As from the Determination Coeficient Test is showing result of 37.2% while the balance of 62.8% is not being explained in this test. The final conclussion is there is a leveraging influence from variable X (advertising exposure) by Blibli.com toward the variable Y (customers’ buying intention).Pada era abad-21 ini, perkembangan teknologi digital semakin canggih terutama dibidang jual beli secara elektronik atau sebutannya e-commerce. Blibli.com adalah situs resmi e-commerce Indonesia milik PT Global Digital Niaga. Blibli.com senantiasa sudah melayani konsumen selama 10 tahun dengan berbagai produk barang maupun digital. Blibli.com juga memiliki media promosi yang banyak sekali keuntungannya baik dari platform media televisi, papan reklame, hingga digital. Dalam penelitian ini bertujuan untuk mengetahui pengaruh terpaan iklan e-commerce Blibli.com terhadap minat beli konsumen. Penelitian ini menggunakan pendekatan kuantitatif dengan metode pengumpulan data secara kuisioner. Populasi dari penelitian ini adalah Universitas Tarumanagara dengan sampel teknik yang digunakan yaitu simple random sampling yang berjumlah 100 responden. Teknik analisis data yang digunakan yaitu uji normalitas, uji regresi linier sederhana, uji t, dan uji koefisien determinasi. Hasil penelitian yang didapatkan menunjukan terdapat pengaruh terpaan iklan e-commerce Blibli.com terhadap minat beli konsumen dengan uji t yang menunjukkan nilai t hitung 7,611 > t tabel 1,984. Hasil uji koefisien determinasi menunjukan pengaruh sebesar 37,2% sedangkan sisanya 62,8% tidak dibahas dalam penelitian ini. Kesimpulannya terdapat pengaruh dari variabel X (terpaan iklan) Blibli.com dengan variabel Y (minat beli).